Integrating Neck Massage and Progressive Muscle Relaxation: A Comprehensive Approach for Reducing Migraine Disability and Enhancing Quality of Life - Rina Budi Kristiani; Novita Fajriyah; Sosilo Yobel (RSUP Dr. Kariadi, 2025)
BACKGROUND: Migraine is a highly disruptive and common neurological disorder characterized by intense headache and transient somatosensory and motor disturbances that affects approximately 1 billion people worldwide with many common causative factors and often results in disability and reduced quality of life. This study aims to determine the effect of combined neck massage and progressive muscle relaxation therapy on disability and quality of life of migraine sufferers. METHOD: This quasi-experimental study used a pre-test-post-test control group design over eight weeks (May to July 2024), selecting 50 participants aged 18–60 years with migraines for over three months based on ICHD-3 criteria. The study utilized the Migraine Disability Assessment Questionnaire and the Migraine-Specific Quality of Life Questionnaire as instruments. RESULT: The combination therapy of neck massage and progressive muscle relaxation both has a significant effect on reducing the severity, frequency, and duration of migraine attacks, as well as improving migraine-related disability (p =0.000) and quality of life (p-value = 0.001). CONCLUSION: Combination therapy of neck massage and progressive muscle relaxation is effective in reducing migraine disability and improving the quality of life of migraine sufferers.